Potassium Intake Prevents the Induction of the Renin-Angiotensin System and Increases Medullary ACE2 and COX-2 in the Kidneys of Angiotensin II-Dependent Hypertensive Rats - Gonzalez, Alexis A. (Front Pharmacol, 2019)
In angiotensin II (Ang II)-dependent hypertensive rats there is an increased expression of proximal tubule angiotensinogen (AGT), collecting duct renin and angiotensin converting enzyme (ACE), which contributes to intratubular Ang II formation. Ang II acts on Ang II type 1 receptors promoting sodium retention and vasoconstriction. However concurrently, the ACE2-Ang-(1–7) axis and the expression of kallikrein and medullary prostaglandins counteract the effects of Ang II, promoting natriuresis and vasodilation. Human studies demonstrate that dietary potassium (K(+)) intake lowers blood pressure. In this report we evaluate the expression of AGT, ACE, medullary prorenin/renin, ACE2, kallikrein and cyclooxygenase-2 (COX-2) in Ang II-infused rats fed with high K(+) diet (2%) for 14 days. Dietary K(+) enhances diuresis in non-infused and in Ang II-infused rats. The rise in systolic blood pressure in Ang II-infused rats was attenuated by dietary K(+). Ang II-infused rats showed increased renal protein levels of AGT, ACE and medullary prorenin and renin. This effect was attenuated in the Ang II + K(+) group. Ang II infusion decreased ACE2 compared to the control group; however, K(+) diet prevented this effect in the renal medulla. Furthermore, medullary COX-2 was dramatically induced by K(+) diet in non-infused and in Ang II infused rats. Dietary K(+) greatly increased kallikrein immunostaining in normotensive rats and in Ang II-hypertensive rats. These results indicate that a high K(+) diet attenuates Ang II-dependent hypertension by preventing the induction of ACE, AGT and collecting duct renin and by enhancing medullary COX-2 and ACE2 protein expression in the kidney.